Antibacterial activity of piper betle leaves extract against Bacillus Subtilis and Escherichia Coli - Zulkipli, Husna; Mohd Syukri, Nor Farhana Syamimi; Abdullah, Siti Nur Azmu’i; Yaafar, Mohd Rabani (2024)
This study investigates the antibacterial activity of Piper betle, a medicinal plant extensively used in traditional medicine across South and Southeast Asia. The research aims to evaluate the effectiveness of P. betle extracts against two bacterial strains: Bacillus subtilis and Escherichia coli. The study further explores the impact of different extraction times (12, 24 and 36 hours) on the antibacterial efficacy of the plant. Using the agarwell diffusion method, the antibacterial activity was assessed by measuring the inhibition zones around the bacterial cultures. The findings revealed that P. betle extracts exhibit significant antibacterial activity, with the highest inhibition zones observed at 24 hours of extraction. The study also employed Fourier-Transform Infrared Spectroscopy (FTIR) analysis to confirm the presence of bioactive compounds in the extracts such as flavonoids. These compounds are known to disrupt bacterial cell walls and inhibit protein synthesis, contributing to the plant's antimicrobial properties. The results suggest that P. betle holds potential as a natural alternative to synthetic antimicrobial agents, offering promising applications in healthcare, particularly in addressing the challenges of antibiotic resistance. Further research is recommended to optimize extraction methods and quantify the bioactive compounds for broader applications.